2022
DOI: 10.3389/fmicb.2022.884721
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Cronobacter spp. and Salmonella spp. Strains Isolated From Powdered Infant Formula in Chile

Abstract: This study characterized five Cronobacter spp. and six Salmonella spp. strains that had been isolated from 155 samples of powdered infant formula (PIF) sold in Chile and manufactured in Chile and Mexico in 2018–2020. Two strains of Cronobacter sakazakii sequence type (ST) ST1 and ST31 (serotypes O:1 and O:2) and one strain of Cronobacter malonaticus ST60 (O:1) were identified. All Salmonella strains were identified as Salmonella Typhimurium ST19 (serotype O:4) by average nucleotide identity, ribosomal multiloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 116 publications
1
7
0
Order By: Relevance
“…However, C. sakazakii is able to utilize sialic acid enhance its ability to cause systematic infections [36]. NanA has been identified as an antitoxin-encoding gene in C. sakazakii in multiple research works [4,5,38] and was also found in the current study.…”
Section: -Utilization Of Sialic Acidsupporting
confidence: 61%
See 4 more Smart Citations
“…However, C. sakazakii is able to utilize sialic acid enhance its ability to cause systematic infections [36]. NanA has been identified as an antitoxin-encoding gene in C. sakazakii in multiple research works [4,5,38] and was also found in the current study.…”
Section: -Utilization Of Sialic Acidsupporting
confidence: 61%
“…OmpA has been reported as an important cellular adhesion factor in Cronobacter spp. to epithelial and endothelial cells of human and animal origin [5,28,36]. In addition, ompA has also been mentioned as a stress-response-encoding gene, especially osmotic stress [38].…”
Section: -Outer Membrane Proteins (Omps)mentioning
confidence: 99%
See 3 more Smart Citations